Analysis of the Influence of Minimum Wage, Education, Economic Growth, and Investment on Formal Labor Force Absorption in Java - M. Fauzan Elva Said; Wildan Syafitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Employment remains a major challenge for Indonesia, particularly in the Java region. The high and concentrated population growth in Java has led to a continuous increase in the working-age population, thereby expanding the labor supply. However, the absorption of labor in the formal sector tends to be lower compared to the informal sector, which is influenced by various underlying factors. This study aims to examine the effects of minimum wage, education level, economic growth, and investment on the absorption of formal labor in Java. Additionally, a dummy variable is included to control for the impact of the COVID-19 pandemic. The study employs a quantitative method using panel data, consisting of time series data (2015–2023) and cross-sectional data from six provinces in Java. The Random Effect Model (REM) and panel regression analysis are applied. The findings indicate that the minimum wage does not have a significant effect on formal labor absorption, while education, economic growth, and investment have a statistically significant influence